EVIDENCES OF ACTIVE FAULTING IN THRACE REGION (NORTHEASTERN GREECE) - Rondoyanni, Th.; Georgiou, Ch.; Galanakis, D.; Kourouzidis, M. (Bulletin of the Geological Society of Greece, 2004)
Active oblique to strike-slip faults were identified in southern Thrace (northeastern Greece), on the basis of field observations, geological mapping, analysis of geometrical and dynamic characteristics of recent tectonic structures as well as evaluation of their seismic potential. The seismic activity refers mainly to strong earthquakes occurring under the sea, while a minor number of seismic epicenters have been registered on land. According to the historic and recent data, most seismic destructions in this region are due to the influence of the North Anatolian Fault and North Aegean Trough system. The diachronic activity of several faults and the changes in the movement type from clearly normal to oblique-normal or strike-slip, have left clear signs on the existing polished fault planes. Among the numerous faults determined in Thrace, some of them can be characterized as active, according to their geological and morphotectonic characteristics. Taking in to account the faults length, the specific seismotectonic conditions prevailing over the Hellenic territory and the existed empirical relationships, the maximum displacement in case of seismic reactivation was estimated.